Developing Mathematics Learning Media Using Macromedia Flash 8 to Improve Mathematical Concepts Understanding - Sartika, Putri Dwi; Fauziyah, Nur (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2024)
The use of appropriate learning media can help students understand abstract concepts and make learning more meaningful and joyful. This study aims to produce learning media based on Macromedia Flash 8 to improve students' mathematical concepts understanding. The development research used follows the ADDIE model, namely analyze, design, development, implementation, and evaluation. The trial of the product prototype involved 27 seventh-grade students of a junior high school in Gresik, East Java. Data were collected using a validation questionnaire of media and material aspects, a student response questionnaire, and a mathematical concepts understanding test. The data were analyzed using quantitative and qualitative methods. The results of the study showed that the learning media was in the very feasible category in terms of material and media aspects. While practicality was obtained from student responses with a good category. In addition, effectiveness was determined based on an increase in mathematical concepts understanding in the medium category. Thus, the Macromedia Flash 8-based learning media that was developed can be used widely, especially on the topic of algebraic forms.